Efektivitas Ekstrak Daun Sirih Hijau Terhadap Perkembangan Larva Nyamuk di Desa Kuala Langsa - Intan Bahrina; Etika Sari; Dina Suwardi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The vector of dengue fever is the Aedes aegypti mosquito. In 2022, there will be 79 cases of dengue fever in Langsa City. Using chemical insecticides on mosquito larvae can create resistance for the larvae. Therefore, you can use the natural insecticide green betel leaves which contain essential oils, alkaloids, flavonoids, saponins and tannins which are toxic and can affect the digestive system and nervous system of Aedes aegypti larvae. The aim of the research was to determine the effectiveness of green betel leaf extract (Piper betle L) as a natural insecticide. The research method is experimental. The study used 3 concentrations, namely 0.5%, 1% and 1.5% and there were positive control (abate) and negative control, each treatment had 3 repetitions. Each test contained 20 Aedes aegypti larvae and was observed every 4 hours for up to 24 hours. The results showed that green betel leaf extract can kill Aedes aegypti mosquito larvae with a percentage of 95% to 100%. Therefore, green betel leaf extract is effective as a natural insecticide on Aedes aegypti larvae.